The 2007 Provincial Election in Newfoundland and Labrador - Marland, Alex (c/o Institute for Governance Studies, Simon Fraser University, 2007)
On the surface, there was nothing special about the 2007 Newfoundland and Labrador general election, which saw Danny Williams re-elected for a second term as Premier. That his Progressive Conservatives would win a solid majority was never in doubt. There were no emerging issues, major gaffes or innovative campaign tactics, and few tight races. The de facto referendum on Williams’ leadership became a coronation. As Mackinnon (2007: 1) wrote about the Prince Edward Island election held five months earlier, “some campaigns are over before they begin.” In this case the only intrigue was how many Liberal or New Democratic Party candidates would form the opposition. However the results do illustrate that a relatively homogenous electorate can rally around a leader who decries the province’s status in the Canadian federation. Furthermore, when elected officials from all major parties have been implicated in a scandal, many electors respond by not participating in politics. Political scientists can therefore draw comparative insights, such as asymmetrical federalism reminiscent of Quebec Premier Jean Lesage in the early 1960s, political scandal similar to the Grant Devine administration of Saskatchewan in the early 1990s, or about civic engagement generally.